INTERNALISASI NILAI NASIONALISME BERBASIS PANCASILA PADA GENERASI Z DI TINGKAT SEKOLAH MENENGAH ATAS STUDI KASUS SMP SMA SWASTA UTAMA MEDAN - Rotuani Siregar , Natali; Nur Qolbi, Nabila; Dilvinia Siregar , Nira; Triana Sianipar , Melva; Annisa , Nur; Gabriel Siahaan, Parlaungan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the internalization of Pancasila-based nationalist values among Generation Z students at the senior high school level in the context of rapid digital transformation. Technological developments and globalization influence students' mindsets, behaviors, and national identity, presenting both opportunities and challenges in strengthening nationalism. The results show that schools implement a systematic and integrated strategy through classroom learning, habituation activities such as flag ceremonies and extracurricular activities, and social and environmental activities. This approach is supported by contextual learning methods and the use of digital media appropriate to the characteristics of Generation Z. Consequently, students develop a broader and more dynamic understanding of nationalism, not merely as a symbol, but as a collective consciousness to maintain unity, tolerance, and social responsibility. However, various challenges remain, such as the influence of foreign cultures, the uncontrolled flow of digital information, a tendency toward individualism, and a lack of learning innovation. Therefore, strengthening digital literacy, innovation in learning, and collaboration between schools, families, and the community are necessary so that Pancasila values can be effectively internalized and become part of students' character in the digital era.